Subtype-specific prognostic implications of plasma-detected PIK3CA mutations in Vietnamese breast cancer patients - Thao, Dinh Thi; Quyen, Dong Van; Song, Le Huu; Trung, Ngo Tat (Frontiers in Oncology, 2025)
BackgroundPIK3CA mutations are among the most frequent genomic alterations in breast cancer (BC), contributing to disease progression and therapeutic resistance. Non-invasive blood assays can reveal tumor-specific DNA alterations, enhancing personalized oncology.AimThis study aims to investigate the clinical relevance of plasma-detected PIK3CA mutations in Vietnamese breast cancer patients, with a focus on subtype-specific outcomes.MethodsPIK3CA hotspot mutations (H1047R and E545K) were detected in plasma from 196 BC patients. Associations with clinicopathological features and progression-free survival (PFS) were assessed.ResultsPIK3CA mutations were identified in 42.9% of patients with H1047R (31.6%) more prevalent than E545K (15.3%). Mutation rates were highest in HR+ subtypes and elevated in advanced or irradiated patients (p = 0.009). E545K was enriched in HR+ cases, while H1047R was more frequent in HER2+ tumors following radiotherapy. Among metastatic BC patients, those with PIK3CA mutations had shorter PFS (median, 7.0 vs. 15.0 months; p = 0.022), and univariate Cox regression showed increased progression risk (HR = 2.16), although not significant after multivariate adjustment. E545K was associated with lung (p = 0.047) and bone metastases (p = 0.012) and H1047R was enriched in brain metastases (p = 0.028).ConclusionPlasma-detected PIK3CA mutations, particularly E545K and H1047R, exhibited subtype-specific associations with clinical outcomes, indicating that plasma analysis may provide complementary information for prognostic assessment in metastatic BC.